#TITLE_ALTERNATIVE# - ARDIANSYAH (NIM : 10109080); Pembimbing : Dr. Muchtadi Intan Detiena, TOMY
Cryptography is a study of how to secure exchange of messages on an insecure channel. In February 2005, National Security Agency (NSA) issued a documment known as Suite B, which recommends the use of Elliptic Curve Cryptography, because Elliptic Curve Cryptography can provide a higher level of security with smaller key sizes. Elliptic Curve Cryptography (ECC) schemes are public-key mechanisms which security is based on the elliptic curve discrete logarithm problem (ECDLP). One of the strongest attacks on ECC is the attack using the Pollard Rho method. This work gives experimental results on speeding Pollard Rho method for elliptic curves over binary fields using Negation and Frobenius Maps.